Evaluation of the acid-neutralizing and cytotoxicity properties of novel plant mucilage used as an alternative treatment for peptic ulcers and as antacids in Namibia - Shatri, Albertina Mariina Ndinelao (Acta Scientiarum. Biological Sciences, 2023)
Hypersecretion of gastric acid damages the stomach lining, causing the formation of peptic ulcers. Mucilage from medicinal plants offers a relaxing and soothing effect to the endodermal lining of the gut and has antacid properties, which can protect the mucosal lining from gastric acidity. This is the first report aimed to evaluate the physicochemical characteristics, acid-neutralizing, and cytotoxicity properties of traditionally used aqueous mucilage from Asparagus exuvialis and Sesamum capense. The physicochemical properties were determined by biochemical methods. Acid neutralizing and buffering capacities were determined by titration methods. Normal mouse embryonic fibroblast cells were used for cytotoxicity evaluation by MTT assay. The physicochemical characterization confirmed the presence of carbohydrates, alkaloids, saponins, proteins, tannins, flavonoids, and glycosides. Sesamum capense mucilage exhibited the most potent artificial gastric juice neutralizing capacity pH of 4.62±0.01, 8.0±0.00 acid neutralization capacity per gram of acid, and 30 minutes duration of acid neutralization. The aqueous mucilage from S. capense did not cause any significant cytotoxicity to 3T3 cell lines showing an IC50 value of 91.5 ± 0.06 μg mL-1, confirming the safe nature of the mucilage. These findings revealed that S. capense has the potential to neutralize gastric acid responsible for ulceration and can be safely consumed.